2017
DOI: 10.1158/1078-0432.ccr-17-1231
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Navitoclax Sensitivity by Dihydroartemisinin-Mediated MCL-1 Repression in BCR-ABL+ B-Lineage Acute Lymphoblastic Leukemia

Abstract: Purpose BCR-ABL+ B-ALL leukemic cells are highly dependent on the expression of endogenous anti-apoptotic MCL-1 to promote viability and are resistant to BH3-mimetic agents such as navitoclax (ABT-263) that targets BCL-2, BCL-XL, and BCL-W. However, the survival of most normal blood cells and other cell types are also dependent on Mcl-1. Despite the requirement for MCL-1 in these cell types, initial reports of MCL-1-specific BH3-mimetics have not described any overt toxicities associated with single-agent use,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…Our lab has previously shown that the anti-malarial drug dihydroartemisinin (DHA) can repress MCL-1 translation and synergize with the BH3-mimetic ABT-263 (22). Here, we show mechanistically that DHA induces the repression of MCL-1 through activation of a Heme-sensing pathway dictates apoptotic response 5 cellular heme-sensing pathway that results in eIF2α phosphorylation and subsequent attenuation of protein translation.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Our lab has previously shown that the anti-malarial drug dihydroartemisinin (DHA) can repress MCL-1 translation and synergize with the BH3-mimetic ABT-263 (22). Here, we show mechanistically that DHA induces the repression of MCL-1 through activation of a Heme-sensing pathway dictates apoptotic response 5 cellular heme-sensing pathway that results in eIF2α phosphorylation and subsequent attenuation of protein translation.…”
Section: Introductionmentioning
confidence: 78%
“…Previous efforts to mechanistically address how DHA triggered the repression of MCL-1 revealed a gene expression signature consistent with the induction of the endoplasmic reticulum (ER) stress pathway (22). To further interrogate this pathway, the three canonical branches of the cellular ER stress pathway were genetically ablated in mouse p185 + Arf-null B-ALL (hereafter referred to as BCR-ABL + B-ALL) using CRISPR/Cas9 targeting (Sup.…”
Section: Crispr Screen Identifies Pathways Required For Dha Induced Amentioning
confidence: 99%
See 3 more Smart Citations